Has canopy height and biomass recovered 78 years after an intense fire in south-Western Australia's red tingle (Eucalyptus jacksonii) forests? - Wardell-Johnson, Grant; Crellin, L.; Napier, C.; Meigs, G.; Stevenson, A.; Wong, S. (CSIRO PUBLISHING, 2017)
Â© IAWF 2017. Tall eucalypt old-growth forests are notable for their large, old (i.e. venerable) trees and have both significant conservation value and high carbon stores. We investigated whether canopy height and biomass had recovered in an old-growth red tingle (Eucalyptus jacksonii) forest 78 years after a high-intensity fire. We recorded species, diameter, hollow butting and height of all 596 trees > 10-cm diameter at breast height, as well as fine and coarse woody debris, in a 3.55-ha plot near Nornalup, south-Western Australia. Pre-fire canopy height was estimated by allometrics derived from tree height and diameter, and diameter and length of recently fallen branches. Of the basal area (75.0m2 ha-1), 92.7% was eucalypt (chiefly E. jacksonii), with regeneration accounting for only 8.5% of the total. Although canopy species composition apparently did not change following fire, stand height and biomass had not recovered to pre-1937 levels by 2015. Canopy height remained 5.06m (11%) less and biomass 25% less, 78 years after the fire. The combination of intense fire and a warmer, drier climate appears to have prevented recovery of forest height and structure at this site. These findings indicate that ecologically important, venerable trees are increasingly vulnerable to canopy fire and climate change. Journal compilation